An adaptive approach for recovering overlapping echoes in oil film thickness measurement by ultrasound. Issue 5 (4th September 2017) - Zhang, Kai; Wu, Tonghai; Duan, Zhihe; Meng, Qingfeng; Meng, Qinghu
Abstract : Purpose: For oil film thickness measurement using ultrasonic spring model, obtaining the isolated reflection from the oil film layer is the key point. While for oil film thickness measurement in thrust bearings with thin liner, the reflection from the substrate-Babbitt interface will overlap with the reflection from the oil film layer. This overlapping will render the ultrasonic spring model invalid. To obtain the isolated reflected signal from the oil film layer accurately, an adaptive method was developed to recover the overlapping echoes. Design/methodology/approach: A genetic-algorithm-based support matching pursuit (GA-based SMP) was developed to provide the optimal echo number and initial parameters guesses automatically and efficiently. Then, the traditional expectation maximization (EM) model was used to fine tune the accurate results. Findings: The developed method was tested using both simulated echoes and the overlapping echoes encountered in the ultrasonic oil film thickness measurement of thrust bearings. The results demonstrated that the developed method performed well on recovering overlapping echoes adaptively. Originality/value: The work shows an adaptive method to recover the ultrasonic overlapping echoes. When used in ultrasonic oil film thickness measurement, it can help extend the application of traditional ultrasonic spring model to objects with four or more layers.